Assessment of good manufacturing practice for small scale food industry in Malang region, East Java, Indonesia. (March 2018) - Purwantiningrum, I; Widyhastuty, W; Christian, J; Sari, N
Abstract: Enhancing food safety in developing countries, such as Indonesia, poses more challenges, especially those of the small- and medium-scale. Various food safety systems are available and readily implemented in the food industry. However, to ensure the effectiveness of such systems, pre-requisite programs should be applied prior to the implementation of food safety system. One of the most acknowledged pre-requisite program is Good Manufacturing Practices (GMP). The aim of this study is to assess the GMP compliance of some small-scale food companies in East Java. Three types of traditional food product were selected, include tempe chips, palm sugar, and instant herbal drink. A survey involving three companies for each type of traditional food was conducted. Data was obtained through observation and assessment based on tabulated criteria in GMP criteria. In essential, the result revealed the compliment level of the food companies being surveyed. There was different level of compliment between each type of the food industry, where the palm sugar industry had the lowest level of compliment compared to the other two. This difference is due to the food safety awareness, social and cultural influences, and also knowledge on food safety and hygiene practice.